EFFECT OF MULTI-PASS WELDING ON BEAD GEOMETRY AND HSLA STEEL SURFACE DEFECTS - Maulana Banurea; Maulana Pratama (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
This study explores the impact of the variation in the number of passes in the multi-pass welding process on the shape of the weld bead and the damage to the surface of High Strength Low Alloy (HSLA) steel with a thickness of 8 mm through the arc welding method. The tested welding process includes 1 pass, 2 pass, and 3 passes while maintaining similar welding parameters. The findings of this study indicate that the number of passes has a significant effect on the quality of weld joints. Welding with 1 pass results in alexistoto suboptimal filling, coupled with undercut defects and incomplete fusion. In contrast, 2-pass welding shows the best results with symmetrical bead shapes and very minimal surface damage. However, the application of 3 passes results in an increase in incoming heat, which has an impact on the widening of the beads as well as the appearance of overlap and porosity defects. Therefore, the use of 2 passes is recommended as the most superior option for welding HSLA steel with a thickness of 8 mm.